Dukungan Digital Transformation pada Daya Saing PT Pembangkitan Jawa Bali Services - Goesti Nahru; Yetty Dwi Lestari (Syntax Literate, 2023)
This study discusses the role of digital transformation in achieving sustainable competitive advantage at PT PJB Services, a power plant operation and maintenance services company in the era of the fourth industrial revolution. This study examines the effect of institutional pressure and digital transformation on competitive advantage as well as the mediating role of digital transformation between institutional pressure and competitive advantage. In addition, this study also investigates the moderating impact of innovation capability on the relationship between digital transformation and competitive advantage. Quantitative methods were used in this study using survey design and structural equation modeling (SEM) analysis to test the hypotheses and link the variables under study. The results showed that institutional pressure and digital transformation have a positive and significant influence on competitive advantage. In addition, digital transformation serves as a mediator between institutional pressure and competitive advantage, while innovation capability strengthens the impact of digital transformation on competitive advantage. The findings emphasize the importance of addressing institutional pressures, implementing effective digital transformation, and developing innovation capabilities to achieve sustainable competitive advantage in a rapidly changing and competitive market.